2004
DOI: 10.2337/diabetes.53.2007.s36
|View full text |Cite
|
Sign up to set email alerts
|

Putative Metabolic Effects of the Liver X Receptor (LXR)

Abstract: The nuclear receptors liver X receptor (LXR)␣ and LXR␤ are sensors of cholesterol metabolism and lipid biosynthesis. They have recently been found to be regulators of inflammatory cytokines, suppressors of hepatic glucose production, and involved in different cellsignaling pathways. LXR␣ is a target gene of the peroxisome proliferator-activated receptor-␥, a target of drugs used in treating elevated levels of glucose seen in diabetes. Furthermore, insulin induces LXR␣ in hepatocytes, resulting in increased exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(144 citation statements)
references
References 58 publications
(39 reference statements)
6
133
1
4
Order By: Relevance
“…In recent years our laboratory has established that fetal brown adipocytes constitute an ideal system for studying molecular mechanisms of insulin resistance and for testing novel approaches to overcome or bypass such resistance. One such approach is ligand activation of nuclear receptors, which can regulate glucose metabolism in multiple tissues including adipose tissue [3][4][5]. Accordingly, we decided to explore and compare the effect of nuclear receptor agonists on glucose uptake in brown adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years our laboratory has established that fetal brown adipocytes constitute an ideal system for studying molecular mechanisms of insulin resistance and for testing novel approaches to overcome or bypass such resistance. One such approach is ligand activation of nuclear receptors, which can regulate glucose metabolism in multiple tissues including adipose tissue [3][4][5]. Accordingly, we decided to explore and compare the effect of nuclear receptor agonists on glucose uptake in brown adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…NR1HRs are activated by naturally produced oxysterols, including (22R)-hydroxycholesterol, (24,25S)-epoxycholesterol, and 27-hydroxycholesterol, as well as by synthetic compounds such as T0901317 and GW3965 [1,2]. Although NR1HR function has been elucidated in detail with respect to cholesterol and lipid metabolism, new findings have indicated that NR1HR is an important regulator of glucose metabolism in liver and adipose tissue [3][4][5]. Recent studies have reported low plasma glucose, improved glucose tolerance and increased glucose-induced insulin secretion by islets in genetic and dietary models of type 2 diabetes treated with synthetic NR1HR agonists [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Se ha reportado que algunos RNH tendrían, además, participación fisioló-gica en el metabolismo de los carbohidratos 4,5 , la respuesta inflamatoria local [6][7][8] , la regeneración tisular 9 , la diferenciación celular 10 , la apoptosis 10 y el envejecimiento, ampliando su potencial impacto en la patogenia y el tratamiento de diversas enfermedades.…”
Section: Rev Méd Chile 2005; 133: 1483-1492unclassified
“…Sin embargo, y al igual que PPARß/δ, estos receptores nucleares también han sido implicados en la regulación de procesos tales como la inflamación, el metabolismo de los carbohidratos y la homeostasis energética 5 .…”
Section: Los Receptores Nucleares Lxr Y Fxrunclassified
See 1 more Smart Citation